Agricultural and Food E-Resources Usage at the University of the West Indies (UWI) Mona Campus - Sasekea Yoneka Harris (Bilgi Dünyası, 2013)
An analysis of selected agricultural and food e-resources at UWI Mona Campus indicate only a small percentage of students and lecturers are utilizing these.